2019
DOI: 10.7554/elife.46966
|View full text |Cite
|
Sign up to set email alerts
|

Functional clustering of dendritic activity during decision-making

Abstract: The active properties of dendrites can support local nonlinear operations, but previous imaging and electrophysiological measurements have produced conflicting views regarding the prevalence and selectivity of local nonlinearities in vivo. We imaged calcium signals in pyramidal cell dendrites in the motor cortex of mice performing a tactile decision task. A custom microscope allowed us to image the soma and up to 300 μm of contiguous dendrite at 15 Hz, while resolving individual spines. New analysis methods we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
98
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(112 citation statements)
references
References 117 publications
(216 reference statements)
13
98
1
Order By: Relevance
“…This mechanism is input specific and is efficient only when the coactive synapses are located within ϳ5-10 m distance; it is possible that biochemical compartmentalization contributes to constraining the spatial limits for subthreshold LTP. This small number and spatial scale is remarkably consistent with that of small functional spine clusters observed in several PC types, including CA1 (Sheffield et al, 2017) and cortical PCs (Kleindienst et al, 2011;Takahashi et al, 2012;Iacaruso et al, 2017;Scholl et al, 2017;Kerlin et al, 2019;Lee et al, 2019). Such small clusters are neither necessary (Losonczy and Magee, 2006) nor sufficient to evoke d-spikes even under simulated in vivo conditions (Ujfalussy and Makara, 2020), but this is actually not needed for their local plasticity by the mechanism we describe.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This mechanism is input specific and is efficient only when the coactive synapses are located within ϳ5-10 m distance; it is possible that biochemical compartmentalization contributes to constraining the spatial limits for subthreshold LTP. This small number and spatial scale is remarkably consistent with that of small functional spine clusters observed in several PC types, including CA1 (Sheffield et al, 2017) and cortical PCs (Kleindienst et al, 2011;Takahashi et al, 2012;Iacaruso et al, 2017;Scholl et al, 2017;Kerlin et al, 2019;Lee et al, 2019). Such small clusters are neither necessary (Losonczy and Magee, 2006) nor sufficient to evoke d-spikes even under simulated in vivo conditions (Ujfalussy and Makara, 2020), but this is actually not needed for their local plasticity by the mechanism we describe.…”
Section: Discussionsupporting
confidence: 86%
“…Shorter dendritic segments, with a group of coactive inputs, may also represent integration compartments by producing local NMDARmediated spikes (Polsky et al, 2004). Furthermore, imaging studies revealed spatially restricted Ca 2ϩ signals in vivo, suggesting locally correlated synaptic activity (Kleindienst et al, 2011;Takahashi et al, 2012;Cichon and Gan, 2015;Iacaruso et al, 2017;Scholl et al, 2017;Sheffield et al, 2017;Kerlin et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Here, however several studies support the existence of dendritic plateau potentials in vivo (Lavzin et al, 2012;Xu et al, 2012;Smith et al, 2013;Gambino et al, 2014;Cichon and Gan, 2015;Du et al, Ranganathan et al, 2018). Significantly, two recent studies (Moore et al, 2017;Kerlin et al, 2019) reported in vivo plateau potentials with characteristics directly comparable to the biophysics of the plateau potentials discussed in the present study. Glia-encapsulated-tetrode in vivo recordings showed large-amplitude, sustained plateau depolarizations (lasting several hundred milliseconds) accompanied by sodium spikes (ref.…”
Section: Distortion Of the Neuronal R In And Tau By Simple Depolarizasupporting
confidence: 79%
“…Second, our result that global plasticity can contribute to the weakening of other synapses when the cell is driven by the activation of clustered inputs can promote new theoretical and experimental research investigating the interaction between local and global plasticity rules in shaping neuronal feature selectivity and cluster formation 65 . Third, our insights could motivate novel in vivo experiments both to further quantify the mid-scale organisation and diversity of synaptic inputs targeting the dendritic tree (focusing less on the fine-scale within-branch arrangements 5,6 ), as well as to directly test predictions of our simulations.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the spatial scale of the synapses showing correlated activity in vivo has been found to be restricted to~5-10 μm and involved a small number,~2-5 dendritic spines 2,[4][5][6] . This is substantially less than the~10-20 inputs required to trigger dendritic Na + or NMDA spikes (characteristic for thin branches) under in vitro conditions 7-10 leaving the potential impact of the clusters elusive.…”
mentioning
confidence: 99%